Pengembangan Media Pembelajaran Cekatan Berbasis Permainan Teka-Teki Silang (Tts) Pada Cerita Fabel Untuk Meningkatkan Kemampuan Literasi Siswa Kelas 2 Sekolah Dasar - Ornella Alika; Sulianto, Joko; Sutono, Agus (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop CEKATAN learning media, a crossword puzzle-based media with fable content, to improve the literacy skills of second-grade elementary school students. The research employed Research and Development (R&D) with a modified Borg & Gall model up to the limited trial stage. The participants were students from both experimental and control classes at Wringinputih 01 Public Elementary School, Semarang Regency. Research instruments included validation sheets from experts, teacher and student questionnaires, and literacy tests in the form of pretest and posttest. Data were analyzed using descriptive statistics to measure validity and practicality, and inferential statistics (normality, homogeneity, t-test, and N-Gain) to measure effectiveness. Validation results indicated that CEKATAN media was highly valid, with material experts rating it at 93.3% and media experts at 90.6%. Practicality was rated very high by both teachers (92.7%) and students (94.2%). Effectiveness tests showed significant differences between the experimental and control classes (Sig. 0.000 < 0.05). The N-Gain score for the experimental class was 0.84 (high category), while the control class obtained 0.40 (moderate category). These findings demonstrate that CEKATAN media is valid, practical, and effective, making it suitable to be applied in elementary school literacy learning. These findings further imply that CEKATAN media has the potential to support school literacy programs and can be implemented more broadly in elementary education as a sustainable approach to fostering students’ reading interest and comprehension.